Nuclear Data Sheets for A = 90 - Basu, S.K.; Mccutchan, E.A. (Nuclear data sheets, 2020)
The experimental results from the various reaction and decay studies leading to nuclides in the A = 90 mass chain have been reviewed. These data are summarized and presented, together with the adopted level schemes and properties, for the nuclides from Ge(Z = 32) through Pd(Z = 46). This evaluation replaces the previous evaluation by E. Browne, which appeared in Nuclear Data Sheets 82, 379 (1998).